Afro-guianenses em Boa Vista : língua, religião e arte - Braga, Ana Paula Araújo (2015)
This search aims to produce knowledge about the complexities that forms when corroborated the social ethnic factor, whose mediation to international migration, which affects inquires and carefull investigations. Ethinic identity presentend by african-Guyanese immigrants in the city of Boa Vista, is which central object of study in this research and had been observed that the same functions as stigma element evidenced by a share of the resident Brazilians population, reflecting an imaginary imbued with negatives references in relations on the cultural ethnic groups that come from source outclassed by the condition social found in Latin American countries. As analysis criteria for this study, are the chapters that were developed from participatory observation in places that immigrants interlocutors exercised some professional and religious activity, and therefore, the dissemination of markers points migration of african-Guyanese to Boa Vista. Having noticed that this stigma, by presented in subtle, level, it might be easily seen as something “normal”, and how these immigrants turn through their social identity (English ancestry) to reframe ethnic identity, which is inserted African descent and thus, try to reverse the stigmatized image inculcated by social, economic and above ethnic and racial. In contemporary times, the issues have been recurrent to explain the disctinctions occurring in social relations that scattered on the empirical and streamiling itself over time to adapt to the environment in which to share the cultural elements of each group